The Profile of Students’ Pedagogical Knowledge on the Implementation of Mentoring Programts’ Pedagogical Knowledge on the Implementation of Mentoring Program - Nopriyeni Nopriyeni; Endang Sulaiman (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims at revealing the students’ pedagogical knowledge on the implementation of a mentoring program. There were 60 students of Biology Education Study Program from Muhammadiyah University of Bengkulu involved in this study. The students’ pedagogical knowledge is considered as students’ competency within five aspects (Knowledge of learning processes, Knowledge of individual characteristics, Knowledge of classroom assessment, Knowledge of teaching methods, Knowledge of classroom management). The instruments for data collection were essay tests which had been validated through the expert judgment. The scores representing the students' pedagogical knowledge were categorized into three categories (low, medium, and high). The collected data were analyzed using a descriptive quantitative approach. The results of the study reveal the students' competency in the ten indicators of pedagogical knowledge consisting of  learning strategies (85%); feedback provision to students (76%); knowledge of cognitive development (78%); motivatingstudents (70%); formative and summative assessment (73%); lesson plan evaluation (78%); various teaching methods (73%); appropriate teaching method (83%); conditioning a conducive atmosphere (80%); classroom management (86%). Thus, it can be concluded that the students' pedagogical knowledge on the implementation of a mentoring program can be categorized as high and able to improve their experiences of teaching practices as prospective teachers.